SENTINEL LYMPH NODES IN ENDOMETRIAL CANCER - A. I. Berishvili; O. V. Li; T. M. Kochoyan; N. V. Levkina; R. A. Kerimov; S. B. Polikarpova (Опухоли женской репродуктивной системы)
Endometrial cancer (EC) typically is treated surgically. Because of the adjuvant treatment implications, complete surgical staging including lymphadenectomy is recommended for high-risk ECs. Sentinel lymph node mapping has the potential to provide information about lymph node metastasis while avoiding potential complications of extended lymph node dissection.